The influence of demographic characteristics of consumers on decisions to purchase technical products - Puška, Adis; Stojanović, Ilija; Šadić, Sead; Bečić, Haris (The European Journal of Applied Economics, 2018)
The term consumer behavior has become very popular in recent studies. It is characterized by various processes, with consumers purchasing decisions being one of them. This paper explores the way in which demographic characteristics influence purchasing decisions with focus on technical products including household appliances, computers, TV sets and similar technical products that cost more than 400 BAM. The empirical study was conducted in the region of northeast of Bosnia Herzegovina and 192 respondents were included in the study to express their allegations of purchasing decisions. Factor analysis was used to identify broader constructors as a basis for observation of the variables. In total, six variables were identified. Based on the calculation of Cronbach’s Alpha indicators, it has been established that there was a low internal affiliation of claims in two variables, upon what they were discarded. Thus, four variables were used to study purchasing decision-making. The results of multivariate analysis of variance (MANOVA) showed that gender, income level and employment status of the respondents significantly influence purchasing decisions among consumers. The analysis of variance (ANOVA) has further shown that females Under the age of 25 and whose income is less than 400 BAM with less than 25 years are generally dedicating to purchasing decisions. The empirical findings showed that the most satisfied with their purchasing decisions are male respondents, whose income varies between 400 BAM and 800 BAM and who belong to the category of students under 25 years.